Effect of Age, Length of Service and Education on Employee Productivity PT Jasa Raharja Medan - Lakshmita, Sandra; Simanjorang, Yohana Rohan Auli; Fangestu, Ferdian; Mirza, Deni Faisal (International Journal Of Economics Social And Technology (IJEST), 2024)
This study aims to examine the effect of age, tenure, and education on employee productivity, either partially or simultaneously. Direct testing and questionnaire distribution obtained a population of 48 people, followed by statistical correlation tests and simple regression. The partial hypothesis test obtained the value of Age (X1) tcount < t table or 0.996 < 1.201063 and significant obtained 0.325 < 0.05, Working Period (X2) obtained tcount value > ttable or 1.539 > 1.201063 and the relevant value obtained was 0.131 < 0.05 and Education (X3), the value of tcount < t table or 0.573 < 1.201063 and the relevant value obtained 0.570 < 0.05 on employee productivity (Y). After conducting the test, it was concluded that partially Age, Term of Service, and Education had a positive and relevant impact on the productivity of PT Jasa Raharja's Medan City employees. Overall Age, Working Period, and Education have a very positive and significant impact on the productivity of employees of PT Jasa Raharja Medan.